PENEGAKAN HUKUM TINDAK PIDANA PERDAGANGAN ORANG YANG DIPEKERJAKAN SEBAGAI PEKERJA SEKS KOMERSIAL DI PROVINSI RIAU - S, Farezza Alfashih; Firdaus, Emilda; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Human trafficking is the most evil problem compared to other violent activities, because traffickingmostly uses violence against victims. Trafficking in the Riau Regional Police is still common and has a largenumber of victims. Meanwhile in Indonesia there is an independent supervisory agency that functions inconducting law enforcement and the institution is the Indonesian National Police. The purpose of writingthis thesis, namely; First, to find out law enforcement against trafficking in persons employed as commercialsex workers in Riau Province. Second, to find out the obstacles in law enforcement of trafficking in personsemployed as commercial sex workers in Riau Province. Third, to find out how the efforts made in lawenforcement against trafficking in persons employed as commercial sex workers in Riau Province.This type of research can be classified in the type of sociological juridical research, because in thisstudy the authors directly conduct research at the location or place of study in order to provide a completeand clear picture of the problem under study. This research was conducted at the Riau Regional Policeoffice, while the population and sample are all parties related to the problem examined in this study, thedata sources used, primary data, secondary data and tertiary data, data collection techniques in this studywith interviews and library study.From the results of the study there are three main things that can be concluded. First, lawenforcement of trafficking in persons employed as commercial sex workers in Riau Province is carried outin a pre-emptive, preventive and repressive manner. The second obstacle in law enforcement againsttrafficking in persons employed as commercial sex workers in Riau Province is the discovery of internal andexternal constraints. Third Efforts are made to overcome obstacles in law enforcement of trafficking inpersons employed as commercial sex workers in Riau Province by increasing performance in units andovercoming problems both internally and externally.The author's advice, first, should be to maximize performance and professionalism so thatexpectations in law enforcement are created. Second, to overcome obstacles in law enforcement, RiauRegional Police are expected to be consistent in carrying out their duties and need to improve thecoordination function, functions in various units and internal improvements consistently and sustainably.Third, efforts are made to overcome obstacles in law enforcement to be more directed and increased again.Keywords: Law Enforcement-Crime-Trafficking in Persons.